(3CSO GdZGHg aj eYQaI GdUMGHgs - (3Ydj Hf eMeO Hf YHO GdcQje Hf YHO GdhGMO GdTjHGfj GdLRQj, CHh GdMSf YR GdOjf GHf GdCKjQ,J (B630 (3g` s ((3YHOGdZfi Hf YHOGdeDef Hf EHQGgje Hf HOQ CHj GdYScQ GdHjGJi s)
(3ChdgG (B:s
(3bGd GdTjN GHf GdCKjQ GdMeO ddg GdPi gOGfG dgPG heG cfG fgJOi dhdG GeG HYO adG Yde CTQa ef Yde GdTQjYI s
(3BNQgG (B:s
(3hcGf Sehjg ef Ggd GdHdbGf fUQGfjkG TeGSkG, aCSde hMSf ESdGeg hYGT YTQhf heGFI Sfg fLR GdLRA GdChd s
(3GdLRA GdChd ef fSNI NRGFfjI fajSg hjHOC ef Chd GdcJGHs
(3GdfSNI HgG MhGTs
(3GfXQ GdChd ef GdJGQjN Qbe (B29s
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJGQjNs